Contribuições para a Utilização Inovadora da Tecnologia da Informação e Comunicação no Tribunal de Contas do Estado de Mato Grosso do Sul - Diogo Sant'Ana Salvadori (2023)
The need to control management and public spending, which in Brazilian states is carried out by the State Audit Courts (TCEs), generates a high volume of documents and information to be analyzed. The expansion of information and communication technologies (ICTs) offers an opportunity to help these bodies increase their information processing and oversight capacity. In this context, the aim of this research was to benchmark the TCE-MS against the other State Audit Courts, in order to determine the level of incorporation of ICT into innovation processes in public administration. Through qualitative and quantitative analysis of the Activity Reports for the year 2021, as well as the most recent Strategic Plans of the TCEs and their revenue, expenditure and personnel data, we sought to understand how and what type of innovation the TCEs adopt and how the TCE-MS behaves in relation to the others. Evidence shows that the Courts are initially focused on administrative and service innovations and that the TCE-MS could focus on implementing ICT innovations, since it has the financial margin to do so and its performance can be improved in relation to the others.